PENGEMBAGAN MEDIA PEMBELAJARAN BERBASIS VISUAL DALAM MENGANALISIS HIKAYAT - Sukma Ria Putri; Deliani Deliani; Nila Safina; Rika Kartika (Universitas Islam Sumatera Utara, 2022)
This study used Research and Development (RD) that aimed to develop visual-based learning media in analyzing the saga. The developed learning media meets good qualifications by taking care the quality. The study refers to the simplified Borg and Gall development procedure, thatfocused only at the final product stage. The five steps are (1) needs analysis, (2) product design, (3) design validation, (4) revision, and (5) final product. Data retrieval was obtained from validations of material and media experts. The instrument data in this study was a questionnaire. The data obtained was quantitative that was converted into qualitative. The results of this study are in the form of visual-based learning media, that have been said to be feasible in several stages of research. The feasibility of learning media is in accordance with the results of the validation. The validation of material experts I was “appropriate criteria” or 79%, material experts II also gave “appropriate criteria” or 75%. The validation of media experts I was “very feasible criteria” or 99%, while media experts II also gave “very feasible criteria” or 84%. Based on the results, this learning media is said to be very feasible to be used in the teaching and learning process in schools.